Quasi‐static response of a bottom‐fixed wind turbine subject to various incident wind fields - Astrid Nybø; Finn Gunnar Nielsen; Marte Godvik (Wind Energy, 2021)
Abstract In the design of offshore wind farms the simulated dynamic response of the wind turbine structure includes loading from turbulent wind. The International Electrotechnical Commission (IEC) standard for wind turbine design recommends both the Mann spectral tensor model and the Kaimal spectral model combined with an exponential coherence formulation. These models give deviating wind loads. This study compares these two models to a large eddy simulations model and a model based on offshore wind measurements. The comparisons are performed for three situations, covering unstable, neutral and stable atmospheric conditions. The impact of the differences in the wind fields on the quasi‐static response of a large bottom‐fixed wind turbine is investigated. The findings are supported by an assessment of the impact of individual wind characteristics on the turbine responses. The wind model based on measurements causes high tower bottom and blade root flapwise bending moments due to a high wind load at very low frequencies. Low and negative horizontal coherence is obtained using the Mann spectral tensor model. This causes relatively large yaw moments as compared to the results using the other wind models. The largest differences in response are seen in the stable situation. We furthermore show that the quasi‐static wind load has great impact on the total damage equivalent moments of the structure. From the results, we conclude that in the design of large offshore wind turbines one should carefully consider the structure of the turbulent wind. Further, longer simulations than recommended by the standards should be used to reduce uncertainty in estimated response.